Cost-efficient, true silicone printer with variable material spectrum for individualized medical applications - Martin, Sina; Gugel, Lukas; Martin, Thomas; Preis, Alexander; Reitelshöfer, Sebastian; Franke, Jörg (Procedia CIRP, 2021)
Due to their beneficial material properties, silicones have become increasingly important in the healthcare sector. However, common manufacturing techniques like injection molding are limited. Hence, silicones have become more interesting for additive manufacturing, as it is possible to freely shape individualized products in small quantities. We present a syringe printer architecture for personalized manufacturing of medical products that allows a variable mixing ratio for RTV-2 crosslinking silicones and precise dosing. Compared to other printing methods, various commercially available one or two-component silicones with variable part viscosities can be printed in a broad range from 10-3Pas up to 10³ Pas.
Keywords: Additive manufacturing; individualized healthcare; silicone printing; medical grade silicones